Time in bed of patients undergoing a cardiac procedure, baseline results of the PACO study - Vilkki, Viivi (My University, 2023)
Sleep affects cardiovascular health in many ways, and for example, a connection between sleep disorders and coronary artery disease has been discovered. The aim of this study is to investigate the sleep of patients undergoing a cardiac procedure and compare it with healthy Finnish controls sleep. The study is based on the baseline results from the PACO study (Personalized intervention to increase physical Activity and reduce sedentary behaviour in rehabilitation after Cardiac Operations). The study population consists of 265 cardiac patients divided into four groups based on the cardiac procedure: coronary intervention or coronary angiography, isolated coronary artery bypass grafting, aortic valve replacement and mitral valve surgery. Patients carried an accelerometer seven days preoperatively. During the day the accelerometer was on the hip and at night it was moved to the wrist to optimize sleep monitoring. The accelerometer data was analyzed to calculate patients time in bed (TIB) and TIB was divided into three different categories based on how many movements occurred within a certain epoch. The controls were from the population based FinFit2017 study, matched for age and gender, and their sleep had been monitored with similar accelerometer. The study revealed that the TIB and the time awake in bed was statistically significantly longer in study population than in controls, but no clear differences were noticed in the amount of sleep. This may indicate that heart patients try to get more sleep than general population but take longer to fall asleep or wake up more at night.
Keywords: sydäntoimenpide, uni, kiihtyvyysanturi